Letter (copy) - Citrine, Walter, 1887-1983
030-0132-001 International WMC/WJB/AC/565 29th June, 1938. Mr. W. Schevenels, International Federation of Trade Unions, 9, avenue d'Orsay, PARIS, VIIe Dear Comrade Schevenels, ASTURIAN MINERS' ORPHANS. As intimated to you on the telephone this afternoon, the Mineworkers' Federation of Great Britain has authorised a levy on its membership for the purpose of relief work for the orphans of the miners of Asturias, etc. It has appointed a sub-committee to deal with the allocation of these monies, and this sub-committee will be attending here on Tuesday morning next, at 11 a.m., with the object of securing advice on the questions involved. The Federation welcomed the suggestion that you should be invited to be present, and I am glad to know that you are making it convenient to attend the meeting. Yours faithfully, General Secretary. 292/946/30/132